2011
DOI: 10.3389/fnmol.2011.00005
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen, a Key Factor Regulating Cell Behavior during Neurogenesis and Cerebral Diseases

Abstract: Oxygen is vital to maintain the normal functions of almost all the organs, especially for brain which is one of the heaviest oxygen consumers in the body. The important roles of oxygen on the brain are not only reflected in the development, but also showed in the pathological processes of many cerebral diseases. In the current review, we summarized the oxygen levels in brain tissues tested by real-time measurements during the embryonic and adult neurogenesis, the cerebral diseases, or in the hyperbaric/hypobar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 105 publications
1
48
0
1
Order By: Relevance
“…These levels are finely tuned and if altered could lead to irreversible damages in brain functions (Masamoto and Tanishita, 2009). The in vitro beneficial effects of low O 2 tensions similar to physiological levels on cell survival, proliferation and differentiation in neural precursor cells has been previously reported ((Review Zhang et al, 2011)). Furthermore, mild hypoxic conditions can increase the generation efficiency of iPSCs from human somatic cells (Yoshida et al, 2009).…”
Section: Introductionmentioning
confidence: 85%
“…These levels are finely tuned and if altered could lead to irreversible damages in brain functions (Masamoto and Tanishita, 2009). The in vitro beneficial effects of low O 2 tensions similar to physiological levels on cell survival, proliferation and differentiation in neural precursor cells has been previously reported ((Review Zhang et al, 2011)). Furthermore, mild hypoxic conditions can increase the generation efficiency of iPSCs from human somatic cells (Yoshida et al, 2009).…”
Section: Introductionmentioning
confidence: 85%
“…In this regard, the SGZ contains a rich plexus of blood vessels (42), which are one of the important components of the neurogenesis niche (14). A decrease in oxygen concentration around the vessels due to CO poisoning might thus jeopardize tissue microenvironment for the maintenance of neural stem cell characteristics in the SGZ (43). The HBO has recently been demonstrated (44) to enhance hippocampal neurogenesis in late stage ischemic stroke, via activation of the redox-sensitive hypoxiainducible factor-1α (HIF-1α)/β-catenin pathway, signaling implicated in differentiation of embryonic and neural stem cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also reported an HBOT-mediated stimulation of angiogenesis and neurogenesis following TBI [30], [31].…”
Section: Introductionmentioning
confidence: 91%